2023
DOI: 10.1101/gad.350298.122
|View full text |Cite
|
Sign up to set email alerts
|

Noncatalytic regulation of 18SrRNA methyltransferase DIMT1 in acute myeloid leukemia

Abstract: Several rRNA-modifying enzymes install rRNA modifications while participating in ribosome assembly. Here, we show that 18SrRNA methyltransferase DIMT1 is essential for acute myeloid leukemia (AML) proliferation through a noncatalytic function. We reveal that targeting a positively charged cleft of DIMT1, remote from the catalytic site, weakens the binding of DIMT1 to rRNA and mislocalizes DIMT1 to the nucleoplasm, in contrast to the primarily nucleolar localization of wild-type DIMT1. Mechanistically, rRNA bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…After DIMT1 eliminated, ribosome profiling of AML cells showed dysregulated transcript subsets, indicating that DIMT1 may influence a variety of cancer pathways and malignancies, including leukemia. 79 Our findings indicated that DIMT3 gene expression was lower in AML patients as compared to the control group, which is similar to results in the literature. RPL17-C18orf32 , another ribosomal protein, was decreased in AML patients with high beta-catenin levels, compared to the control group in our study for the first time.…”
Section: Discussionsupporting
confidence: 91%
“…After DIMT1 eliminated, ribosome profiling of AML cells showed dysregulated transcript subsets, indicating that DIMT1 may influence a variety of cancer pathways and malignancies, including leukemia. 79 Our findings indicated that DIMT3 gene expression was lower in AML patients as compared to the control group, which is similar to results in the literature. RPL17-C18orf32 , another ribosomal protein, was decreased in AML patients with high beta-catenin levels, compared to the control group in our study for the first time.…”
Section: Discussionsupporting
confidence: 91%